Detection and molecular characterization of porcine kobuvirus in piglets in 2009–2013 in northern Thailand - Chuchaona W. (2017)
© 2017, Springer Science+Business Media Dordrecht. A total of 636 fecal samples collected from piglets with and without diarrhea during 2009 to 2013 were tested for porcine kobuvirus by RT-PCR. From a total of 528 fecal samples collected from piglets with diarrhea and 108 from healthy controls, 505 (95.6%) and 104 (96.3%) were positive for porcine kobuvirus, respectively. The detection rates of porcine kobuvirus were remarkable equally high in both diarrheic and healthy piglets. Phylogenetic analysis revealed that porcine kobuvirus strains detected in both symptomatic and asymptomatic piglets were genetically closely related to each other and also to other porcine kobuviruses reported worldwide. It was interesting to point out that one of the porcine kobuvirus strains isolated from piglet in our study was similar to a porcine-like bovine kobuvirus reference strain isolated previously in South Korea. This finding provided the evidence to support the interspecies transmission of kobuviruses between cattle and swine.